Asymmetric Synthesis of Trifluoromethylated Amines and Their Derivatives - Cheng, Gui-Lin; Wang, Hui; Lin, Xian-Fu; Wu, Qi (Current Organic Synthesis, 2016)
Trifluoromethylated amines, especially optically active ones, are very important synthetic building blocks in the design of bioactive products. Over the past decades, the development of highly efficient methods for asymmetric synthesis of Trifluoromethylated amines and their derivatives has attracted a continuing interest. A brief overview will give an insight into the asymmetric synthesis of trifluoromethylated amines and their derivatives from trifluoromethyl imines, nucleophilic trifluoromethylation tamed, fluorine-containing allylic esters, and by enzymatic catalysis.
Keywords: asymmetric synthesis